Physical activity in 25-57 year old inhabitants of the Ústí region in relation to employment - Ladislav Bláha; Karel Frömel (Palacký University Olomouc, 2011)
BACKGROUND: The social and health conditions in the inhabitants in the Ústí region are generally considered the worst in the Czech Republic. The high rate of unemployment there is to be considered as one of the significant factors of socio-economical status. AIM: The aim of the study was to analyze the relationship between physical activity (PA) in the adult population, the unemployment and other sociodemographic factors. Further, to identify information that could be used in formulating regional health policy and in the promotion of healthy and physically active lifestyle in the adult population. METHODS: In total, 467 women and 360 men aged 25-57, randomly selected, participated in the study. PA was estimated for last seven days using the IPAQ questionnaire. The PA structure included job related activities, transport, and recreational activities. Further, we estimated vigorous, moderate and walking activities. The data for each PA type and PA intensity were analyzed for the employed and the unemployed men and women. To carry out the statistical analysis, we used the Kruskal-Wallis test, and the logistic regression analysis. RESULTS: The results have confirmed that men perform more physical activity than women (both employed and unemployed) at work and more vigorous PA. On the other hand, both employed and unemployed women were more physically active at home than men. Cycling as a means of transport was used most by unemployed men and walking was the highest in unemployed women. More chances to meet the recommendation of 1200 MET-min of vigorous PA in a week were found in employed men with lower education, unemployed men living in walking and cycling friendly neighborhoods and in inhabitants performing organized PA. Performing moderate PA, the chances to meet the recommendation of 1200 MET-min in a week were found in educated employed people, people living in a family house, employed people owning a dog, and employed people performing organized PA. CONCLUSION: The differences found between PA in employed and unemployed people in the Ústí region can be used when creating re-qualification programs, dealing with issues in social, psychological and health areas especially in the unemployed population.